A PARADIGM SHIFT IN HUMAN RESOURCE ACCOUNTING: INTEGRATING WELL-BEING AND PRODUCTIVITY METRICS - Borah, Amar (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2023)
This research paper explores the paradigm shift in human resource accounting by integrating well-being and productivity metrics. Traditional human resource accounting has primarily focused on financial and quantitative measures, such as training costs and employee turnover rates. However, in the modern workplace, the well-being and productivity of employees are increasingly recognized as crucial factors for organizational success. This paper proposes a conceptual framework that incorporates well-being indicators, such as work-life balance, job satisfaction, and employee engagement, alongside traditional accounting metrics. The research examines the theoretical foundations of well-being and productivity measurement and provides practical guidelines for implementing this integrated approach to human resource accounting.